System Dynamic Simulation Model for Higher Education Strategic Planning - Nurul Nazihah, Hawari; Razman, Mat Tahar (2010)
Strategic planning is vital to higher institution viability. Universities face challenges related to academic affairs, scientific knowledge development, programs quality, market tedencies among others, which make necassary to maintain a continuous learning cycle to check, access, modify, redesign, and restructure policies and procedures in order to meet national accredition standards. A great portion of the existing research on university management problems does not have a quantitative foundation, primarily because such problems involve qualitative (human) elements that are diffult to quantify and model. A truly valuable approach to developing and directing strategy should therefore say something about earnings, not just explaining today's results but showing how to built performance through time. Many institution do not meet their goals because the planning process uses tools that are particulary inadequate for present day environment of complexity and rapid change. The purpose of this paper is to present the conceptual framework for higher education strategic planning problem. This paper aim at matching the System Dynamics metodology with the balanced Scorecard framework toward higher education strategic planning with is believed could significantly improved the planning process in the strategic planning perspective. The potential value of system dynamic for higher education strategic planning is incorporating non linear and iterative view, hard and soft issues, strategic objectives, and changes in educational process. System dynamic approach offers rigorous, fact, based explaintions for performance through time, and confident insights for the future, easily communicated to colleagues and stakeholders.